Relationship Between Level Of Knowledge And Clean And Healthy Living Behavior (Phbs) Among Students At Sma N 3 Salatiga - Herawati, Widya Herawati; Rezania Asyfiradayati (JURNAL KESMAS DAN GIZI (JKG), 2025)
Clean and Healthy Living Behaviors (PHBS) are important promotional and preventive efforts in shaping healthy living habits from adolescence. The purpose of this study is to determine the relationship between knowledge levels and PHBS behaviors among students at State Senior High School 3 Salatiga. Study as a quantitative cross-sectional designed. The population consisted of all 840 students in grades X and XI, with a sample calculated using the Slovin formula of 264 respondents selected using purposive sampling. The study was conducted in April–May 2025 using a questionnaire. Data analysis involved Chi-Square tests and Spearman correlation. The results showed that the majority of knowledge levels were very high (87.1%), and PHBS behavior was categorized as frequent (51.9%) and very frequent (24.6%). There was a significant relationship between knowledge level and PHBS behavior (p = 0.001), with a weak but positive correlation strength (r = 0.169; p = 0.006). The conclusion is that the higher the students' knowledge, the better their tendency toward PHBS behavior. It is recommended that school-based health education be strengthened so that high knowledge is accompanied by consistent practice.